(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
My intention in this paper is to contextualize Danica Marković as a women poet who acts within the dominantly male poetry formation. I define Serbian modernism as a small peripheral literary culture that tends to develop the autonomy of literary field, which was the symptom of modernization and nationalization of a peripheral national literary field. I will point to feminist interpretation of her poetry in the texts written by Biljana Dojčinović and Magdalena Koch, as well as to the interpretation of Radomir Konstantinović. My thesis will be that Danica Marković created a female lyrical „I“ by using the strategies and tactics of male modernist poetry culture in which she participated.